Faktor-Faktor Yang Menentukan Quality Of Work Life Karyawan Magang (Trainee) di Hard Rock Hotel Bali - Hadi, Satria Perwira; Sari, Ni Putu Ratna; Ariani, Ni Made (Jurnal Kepariwisataan dan Hospitalitas, 2024)
Abstract Bali Province is one of the destinations for tourism activities both locally and internationally, this can be proven by the rapid visitation of foreign and domestic tourists who came to Bali Province in the period 2013-2018. With this tourist visit, manpower is needed to support operational and non-operational activities in the tourism industry sector, especially in the tourist accommodation section. However, in this case, it also requires training both in theory and practice for the workforce who will later directly participate in the field work process in the required sector. In this case, apprentices are in the spotlight in the research, this is because the workforce of apprentices has different wages and working life conditions from the workforce of permanent employees. The purpose of this study was to determine the factors that determine the Quality of Work Life of Interns (Trainees) at Hard Rock Hotel Bali. This research is located at Hard Rock Hotel Bali. The data sources used are primary and secondary data sources. The data collection technique used was observation with a participatory approach, interviews, questionnaires, literature study and documentation. The sampling technique used was non probability sampling with purposive sampling type of sample. The data used a Likert scale model with a calibration of the validity and reliability tests. The analysis technique used is the PCA (Principal Component Analysis) method of factor analysis. Based on the SPSS version 17 software, there are 4 factors formed from a total of 10 indicator statements. These 4 factors have a total variance value of 62.734% or rounded to 62.7%, the 4 factors are the communication factor, the compensation factor, the information factor and the last is the work facility factor. The factors that determine are dominated by the communication factor with variance value of 28,195 rounded to 28.2%. Keyword: Quality of Work Life, Internship Employee, Tourist Accomodation, Tourism.